Main complaints identified by parents of children with developmental delays during the initial consultation: a 10-year all-case study - Yasuaki Kusumoto; Eri Takahashi; Kenji Takaki; Tadamitsu Matsuda; Osamu Nitta (PeerJ)
Background In Japan, the child development support initiative is one of the government’s daycare support programs for children with disabilities. Children, aged 0–6 years, who are not attending elementary school can participate in the initiative and receive various support. Reports on the approaches taken by private child development support centers and the guardians’ perceptions are increasing. Conversely, information from public child development support centers, which serve as places for initial developmental consultation, is extremely scarce. Moreover, there are no nationwide reports on the main complaints from each region, which are of concern to the parents. This study aimed to clarify children’s gender and age, presence of referral sources, and characteristics of the main complaints obtained during the initial consultation with parents of children with developmental delays, who used a public developmental support center in a medium-sized city in Tokyo. Methods This study included 1,241 parents of children with developmental delays (average 40.3 months, range 2–87 months). Five questions regarding each child’s characteristics (gender, age in months, and medical diagnosis), referral sources for the use of support centers, and main complaints that they would like to discuss at the initial consultation, were asked. The participants were asked to describe their main complaints (specific consultation details) as precisely as possible. From the free-form descriptions of the main complaints, 137 codes were extracted and grouped into 13 categories. Participants were divided into two groups according to the presence (n = 122) or absence (n = 1,119) of a medical diagnosis. The t-test, chi-square test, and Fisher’s exact probability test were used to examine differences between the two groups. Logistic regression analysis with forced entry was performed to examine whether the factors related to the main complaints raised by parents of children with developmental delays differed depending on the presence or absence of a medical diagnosis. Results The most common chief complaint at the time of the initial consultation was “language development” (43.9%), followed by “childcare and preschool counseling” (15.4%), “hyperactivity/inattention” (13.9%), and “general developmental issues” (13.6%). The regression analysis revealed that gender, age (months), and general developmental issues were factors associated with the presence or absence of a medical diagnosis were gender, age in months, and general developmental issues. The odds ratios (95% confidence intervals) were 1.573 (1.056–2.343) for gender, 0.988 (0.976–1.000) for age (months), and 0.421 (0.200–0.886) for general developmental issues. Conclusion Professionals involved in child development support are expected to have broad knowledge of various developmental issues as well as comprehensive knowledge of local childcare and schooling systems.